EFL Teaching Material Development for Junior High Schools in Arfak Mountains Regency, West Papua - Sukristiningsih Sukristiningsih; Suardi Sahid (Hasanuddin University, 2022)
This Research discusses about teaching attractive materials that are suitable for the students and situation in Junior High Schools in Arfak Mountains Regency. This research aims to identify kinds of teaching attractive materials that suitable to the students and situation in Junior High Schools in Arfak Mountains Regency, and to indicate some types of teaching attractive materials chosen that can be developed by English teachers concerning to availability of the equipment needed in Arfak Mountains Regency. This research used Qualitative method, and the data is collected from observation or interview. The result of this research is found there are only some that might be able to be adopted to use in teaching English in SMP Arfak Mountain Regency. Those are realia, games (board race, Simon says, board jumble race, and hot seat), audio/tapes, and pictures. To develop those types of teaching materials, teachers are expected to be able to create their own teaching materials proposed.